Comparison of Self-Organizing Maps and K-means Algorithms in Grouping Divorce Cases in Yogyakarta City - Priyo Purnomo; Domy Kristomo; Widyastuti Andriyani; Bambang Purnomosidi Dwi Putranto (Journal of Intelligent Software Systems, 2025)
The Religious Court of Yogyakarta serves as the primary judicial body that processes, examines, and renders decisions on civil cases involving adherents of Islam at the initial legal level. The court manages approximately 900 cases annually, with marital dissolution proceedings constituting the predominant category. Categorizing these cases according to marital age and divorce causation is crucial for illustrating the distinctive patterns of divorce within the jurisdiction, thereby informing governmental initiatives promoting family wellness education. For the purpose of data clustering, a comparative analysis was conducted between self-organizing maps (SOM) and K-means methodologies. The research utilized secondary data from 2021, comprising 45 entries of concluded divorce cases. The internal silhouette validation metric established two as the optimal cluster quantity for both analytical approaches. The distribution and attributes of clusters remained largely consistent across both models. Evaluation using the standard deviation ratio revealed superior clustering performance by the SOM method when applied to the divorce case dataset. The analytical results demonstrated that cluster 1 encompassed 11 neighborhoods characterized by elevated divorce rates, while cluster 2 contained 34 regions exhibiting lower to moderate divorce frequencies. The principal determinants shaping divorce case characteristics in Yogyakarta City were identified as "ongoing conflicts and arguments," "abandonment by one spouse," and "financial circumstances."